Modifying hydraulic press brake by variable speed drive application: energy saving, CO2reduction, and economic analysis - Caliskan, Olgun; Akkaya, Ali Volkan (SPRINGER, 2020)
In this study, modifying a constant speed-driven hydraulic press brake machine into a variable speed drive system is examined in terms of electricity saving, CO(2)reduction, and economic perspectives. The goal of the modification is to obtain increased efficiency by adding minimum hardware and software tools. For realizing this goal, a hydraulic test rig operated in a manner to represent the cycle of a specified press brake machine is taken into consideration, which is equipped with a frequency controller on an induction motor and an electro-hydraulic load sensing. Then, the amount of electricity saving is determined experimentally under wide-range operating conditions. Besides, an economic analysis is performed based on 5 different scenarios to represent the conditions of the real industry throughout an operation year. As a result, the amount of electricity saving is observed to vary between 3 and 19% depending on the operating conditions. In addition, it is determined that there is 1.75 to 10.5 tons of CO(2)reduction potential per year. The payback period of the modification investment is computed between 1.51 and 4.67 years, according to the considered scenarios. In the sensitivity analysis, the most important parameters affecting the economic criteria are discount rate, electricity unit price, and initial investment cost.
Keywords: Variable speed; Press brake; Energy saving; Economic analysis; SYSTEM; Science & Technology - Other Topics; Energy & Fuels; Environmental Sciences & Ecology